2022
DOI: 10.3389/fpubh.2022.931480
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pulmonary CT Characteristics of Patients Infected With the SARS-CoV-2 Omicron Variant Compared With Those of Patients Infected With the Alpha Viral Strain

Abstract: BackgroundOmicron has become the dominant variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) globally. We aimed to compare the clinical and pulmonary computed tomography (CT) characteristics of the patients infected with SARS-CoV-2 Omicron with those of patients infected with the Alpha viral strain.MethodsClinical profiles and pulmonary CT images of 420 patients diagnosed with coronavirus disease-2019 (COVID-19) at Ningbo First Hospital between January 2020 and April 2022 were collected. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
(19 reference statements)
3
14
0
Order By: Relevance
“…Recent studies have also shown differences in imaging appearance and severity between breakthrough infections in vaccinated individuals and infections in the unvaccinated, even comparing different vaccine types ( 2 ). Differences in radiological severity of pneumonia between SARS-CoV-2 variants have also been documented previously, including comparisons of the Alpha strain to Omicron ( 3 ), and Omicron to Delta ( 4 ).…”
supporting
confidence: 59%
“…Recent studies have also shown differences in imaging appearance and severity between breakthrough infections in vaccinated individuals and infections in the unvaccinated, even comparing different vaccine types ( 2 ). Differences in radiological severity of pneumonia between SARS-CoV-2 variants have also been documented previously, including comparisons of the Alpha strain to Omicron ( 3 ), and Omicron to Delta ( 4 ).…”
supporting
confidence: 59%
“…Till April 1, 2022, a total of 161 discharged adult patients infected with the Delta variant were included in this study, of which 101 (63%) were male and 46 (29%) presented with pneumonia. The median (IQR) age and baseline 25-hydroxyvitamin D concentration were 37 (28-47) years and 21 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) ng/ml, respectively. There were significant differences in age (34 vs. 43 years; p < 0.001), SARS-CoV-2 IgM titer (0.3 vs. 0.1 AU/ml; p = 0.002), SARS-CoV-2 IgG seropositive (84 vs. 44%; p < 0.001), and titer (82.8 vs. 3.3 AU/ml; p < 0.001), lymphocyte (1.36 vs. 0.87 × 10^9/L; p = 0.002) and platelet count (224 vs. 200 × 10^9/L; p = 0.04), fibrinogen (2.9 vs. 3.3 g/L; p < 0.001), and aspartate aminotransferase (27 vs.…”
Section: Demographic and Clinical Characteristics And Baseline Labora...mentioning
confidence: 99%
“…In the severe form, the failure of immune response may be linked to insufficient type 1 interferon production or signaling, attenuated or skewed adaptive immune response, which may also be due to viral immune escape properties [ 14 ]. Clinical and pulmonary expression differ in patients affected by different variant strains: Yang et al [ 15 ] showed that SARS-CoV-2 Alpha strain mainly affect the lung, while SARS_CoV-2 Omicron affects mainly the upper respiratory tract.…”
Section: Introductionmentioning
confidence: 99%
“…The infection may be associated with episodes of skin rush, joint pain, and gastrointestinal symptoms. Hemolytic disorder related to IgM antibodies producing a cold agglutinin reaction has been reported and cardiac involvement with conductive abnormalities on ECG and congestive heart failures may be uncommon but possible complications [ 15 , 16 , 17 ]. Similar to SARS-CoV-2, M. pneumoniae involves mainly the respiratory tract but systemic organs may also be involved [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation